MEMORIALS. TRANSMISSION AND IDENTIFICATION IN SPAIN AT THE BEGINNING OF THE XXI CENTURY (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
The imminent disappearance of the generation who lived through the civil war and the fear of losing their testimony, has generated new processes of recovery of memory focused on intergenerational transmission. Associations and artists have promoted memorials that, far from constituting immobile landmarks, promote active processes of memory through different strategies. However, their insertion into the public space, where the image of the victim has remained vetoed for decades, has provoked mixed reactions that underline the need to address the study of the recent past. This article analyses these aspects, taking as a starting point six works created during the first years of the XXI century.
Keywords: Memorial, monument, place of memory, historical memory, post-memory